2021
DOI: 10.1111/1750-3841.15801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cedrus deodara extract on the physiochemical and sensory properties of salted meat and its action mechanism

Abstract: The effect of pine needle extract from Cedrus deodara (PNE) on the quality of salted meat was reported, and its action mechanism was further investigated. With the treatment of PNE, the physicochemical properties of salted meat were improved. The peroxide value decreased from 16.18 to 6.78 mmol O2/kg, while the thiobarbituric acid value decreased from 0.79 to 0.40 mg MDA/kg. Moreover, the salted meat with PNE also had the better texture, color, and volatile compositions. The 0.2% PNE group showed the highest Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…As shown in Figure 2c, the fluorescence intensity of myofibrillar protein showed an obvious decline with the increasing concentration of (Xu, Zhou, Yu, et al, 2021). In the present study, tea polyphenol was a water-soluble phenolic compound and contained multiple hydroxyl groups, which could change the tertiary structure of a myofibrillar protein and quench its fluorescence intensity.…”
Section: Fluorescence Spectroscopy Of Myofibrillar Proteinmentioning
confidence: 48%
See 1 more Smart Citation
“…As shown in Figure 2c, the fluorescence intensity of myofibrillar protein showed an obvious decline with the increasing concentration of (Xu, Zhou, Yu, et al, 2021). In the present study, tea polyphenol was a water-soluble phenolic compound and contained multiple hydroxyl groups, which could change the tertiary structure of a myofibrillar protein and quench its fluorescence intensity.…”
Section: Fluorescence Spectroscopy Of Myofibrillar Proteinmentioning
confidence: 48%
“…Commonly, the tryptophan residues are folded and situated in the core of the protein molecule, which contribute to the high fluorescence intensity of protein. So, the conceivable stacking of the benzene rings in phenols and the exposure of tryptophan to the hydrophilic microenvironment are both likely to contribute to the fluorescence quenching of protein (Xu, Zhou, Yu, et al, 2021). In the present study, tea polyphenol was a water‐soluble phenolic compound and contained multiple hydroxyl groups, which could change the tertiary structure of a myofibrillar protein and quench its fluorescence intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al . (2021) also showed that cedrus deodara extract could induce a decrease in POV of salted meat. Similar inhibitory effects in POV values were found in salted silver carp by ZL extract treatment during the processing (Li et al ., 2015a, 2015b) and raw ground pork with persimmon peel extract during chilled storage (Choe et al ., 2017).…”
Section: Resultsmentioning
confidence: 95%
“…Similar changes were observed in a study by Xu et al . (2021), where cedrus deodara extract decreased the fluorescence intensity of MP in salted meat. Huang et al .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation